Relativistic and Close-Coupling Effects in the Spin Polarization of Low-Energy Electrons Scattered Elastically from Cadmium - Bostock, Christopher; Berrington, Michael; Fursa, Dmitry; Bray, Igor (The American Physical Society, 2011)
The measurements of the Sherman function in elastic electron-cadmium scattering by Bartsch et al. [J. Phys. B 25, 1511 (1992)] have been in serious disagreement with scattering theories for nearly two decades. The recently developed relativistic convergent close-coupling method is applied to the problem and found to be in excellent agreement with experiment over the complete energy range measured. The unusually rapid variation in the spin asymmetry parameter in the vicinity of 4 eV projectile energy is now explained in terms of unitarity of the close-coupling formalism.